Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Untuk Meningkatkan Hasil Belajar Pasing Bawah Bola Voli Siswa kelas X SMAN 11 Semarang - Cahya, Septian Ridho Nur; Pradipta, Galih Dwi; Darmanto, Purno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The purpose of this study is the influence of the Teams Games Tournament (TGT) type cooperative model on volleyball bottom passing learning outcomes. This study is a quantitative research that uses an experimental approach with a Teams Games Tournament (TGT) type cooperative learning model. The sampling technique applied is purposive sampling. This study uses a test as an instrument, the test used is the Brumbach Forearm Pass Wall Volley Test. The normality test, homogeneity test, and hypothesis test are the analyses used in this study. Information was obtained that in volleyball underpass skills before the Teams Games Tournament (TGT) type cooperative learning, the lowest score was 40, the highest score was 90, and the average was 65. In the lower passing skills after the Teams Games Tournament (TGT) type cooperative learning, the lowest score was 50, the highest score was 100, and the average was 77. This is also proven based on the comparison of the significance value obtained a score of 0.000 less than the reference of the significance norm of 0.05. The category of the level of learning outcomes of passing volleyball under Class X of SMA Negeri 11 Semarang before being given cooperative learning treatment of the Teams Games Tournament (TGT) type. Based on the results of the study, the conclusion in this study is that the application of learning using Teams Games Tournament (TGT) type cooperative learning to bottom passing in volleyball games in grade X students of SMA 11 Semarang increased by an average of 17.51%.